Obstetric outcomes of teenage pregnancies: A record-based study in a rural hospital of North 24 Parganas district, West Bengal - Sarkar, Paramita; Sarkar, Payel; Sarkar, Arnab; Saibendu Kumar Lahiri (Asian Journal of Medical Sciences, 2024)
Background: Teenage pregnancy is a pregnancy in a woman within 10–19 years of age groups. It results from a number of factors such as early age at marriage, illiteracy, poverty, premarital sex, lack of awareness, and access to contraception. Teenage pregnancy imposes serious social and medical implications relating to both maternal and child health. It is a worldwide public health problem in both developed and developing countries. Aims and Objectives: The study was conducted in a rural hospital of North 24 Parganas in West Bengal. The primary objective was to compare different maternal and perinatal outcomes of teenage primigravida mothers with those of adult primigravida mothers. The secondary objective was to assess the association between various sociodemographic factors on the prevalence of teenage pregnancy. Materials and Methods: The cross-sectional hospital record-based study includes a sample of 78 study subjects each in cases and comparison group. Records were taken from June 2019 to December 2019. Results: Of a total of 379 labor room admissions during the study period, 86 (22.69%) were of the teenage group and 8 cases were excluded from the study. A total of 78 teenage pregnancies were analyzed and compared with 78 adult pregnancies. The mean (standard deviation) age of teenage in our study was 18.10±0.63 and that of the comparison group was 22.74±1.68 years. Results revealed that teenage mothers had a statistically higher proportion of anemia (OR=2.30, P=0.05) and low-birth-weight babies (OR: 3.6, P=0.05) compared to adult-primigravida mothers, respectively. Conclusion: Teenage pregnancy is still a rampant and important public health problem in India with unfavorable perinatal outcomes and needs to be tackled on a priority basis.